The Relationship of Personality Style and Attention Deficit Hyperactivity Disorder in Children - Amos, Stephen P.; Homan, Gretchen J.; Sollo, Natalie; Ahlers-Schmidt, Carolyn R.; Engel, Matthew; Rawlins, Patrice (Kansas Journal of Medicine, 2019)
Introduction. This study was to identify personality correlates of children with a diagnosis of Attention Deficit Hyperactive Disorder (ADHD). The Jungian Personality Type dimensions primarily considered were Sensing/Intuiting and Perceiving/Judging. A Sensing child is likely to be very present-centered. A Perceiving child tends to be curious and resist order and structure. Methods. Children attending a general pediatric clinic with a diagnosis of ADHD were eligible to participate. Enrolled children were administered the Murphy-Meisgeier Type Indicator for Children. Binomial tests were performed comparing Perceiving and Sensing personality components to accepted population rates. Results. Participants (n = 117) were predominantly male (78%) with a median age of 10 years. The Sensing trait (72%) was more prevalent than expected, though prevalence for the Perceiving trait (44%) did not differ from population rates. Conclusions. Personality types occasioned with the diagnosis of ADHD could be useful in establishing/normalizing treatment regimens and approaches to assist these children and their families better. KS J Med 2017;10(2):26-29.